Transformasi Pembelajaran Sejarah melalui Pemanfaatan Teknologi Internet di MA NWDI Gereneng Lombok Timur - Rohman Warabbul Izati Watoni; Abdul Hafiz; Suhupawati Suhupawati (Universitas Hamzanwadi, 2023)
The development of the internet has expanded history learning resources beyond textbooks and teacher explanations, yet its use in madrasahs remains influenced by facilities, teacher competence, and supervision of digital devices. This study analyzes the role and impact of internet technology on history learning at MA NWDI Gereneng, East Sakra, East Lombok. It employed a descriptive qualitative design with an ethnographic orientation. Data were collected through observation, interviews with the principal, history teachers, and students, and documentation from October to November 2022. The data were analyzed by organizing, selecting, categorizing, and interpreting field evidence. The findings show that the internet functions as an additional learning resource, a means of instructional communication, a medium for distance learning, and a driver of learning motivation. It enables students to access Indonesian and world history materials more rapidly and compensates for limited printed worksheets. Its positive impacts include broader knowledge, greater learning autonomy, efficient reference searching, and more varied presentation of historical content. Nevertheless, internet use also creates risks of distraction and access to irrelevant content, requiring teacher supervision, device-use rules, and stronger digital literacy. The effectiveness of internet technology therefore depends not merely on access, but on instructional design, source curation, and pedagogical guidance. Internet use should be directed from simple information searching toward critical, contextual, and responsible history learning.